PERUBAHAN KONFIGURASI RUANG PADA RUMAH BANTUAN PEMERINTAH DI KOMUNITAS ADAT DESA MATOTONAN KEPULAUAN MENTAWAI: PERUBAHAN KONFIGURASI RUANG PADA RUMAH BANTUAN PEMERINTAH DI KOMUNITAS ADAT DESA MATOTONAN KEPULAUAN MENTAWAI - Eljihadi Alfin (Ide dan Dialog Desain Indonesia (Idealog), 2025)
Abstract : The Indigenous Community of Matotonan Village in the Mentawai Islands received government housing assistance totaling 200 units in 2008 and 100 units in 2019. Over time, most of these houses underwent modifications, resulting in changes to their spatial configurations. This study aims to explain the changes in spatial configuration that occurred in the government-assisted houses within the Matotonan Indigenous Community. The research began with a physical survey of all social housing units in Matotonan Village. From this, 10 samples were selected based on two criteria: 1) The house had undergone significant changes and/or featured a unique spatial configuration; 2) The residents were willing to be interviewed and have their homes studied. Data were collected through observing residents’ activities within the home, conducting in-depth interviews with residents and/or their representatives, and thoroughly measuring the house layouts. The measured layout data were illustrated using AutoCAD and CorelDRAW software. The current layout of each sample was then compared with its original design before modifications. The analysis revealed changes in spatial configuration and spatial depth in the social housing units. These changes were primarily due to additional spaces and building mass resulting from an increase in the number of occupants, specific needs for kitchen space, and the requirement for a larger front area. The demand for specific spaces in these houses is closely related to traditional and cultural values. These changes also affected the confex space diagrams, j-graph values, connectivity, and spatial integration. Keywords : spatial configuration changes, government-assisted housing, indigenous community, Matotonan, Mentawai